Competitive Strategies of Vietnamese Higher Educational Institutions - Ngoc, Do Minh (International Higher Education, 2018)
The Higher Educational Reform Agenda (HERA) for the period 2006–2020 is an arduous effort of the Vietnamese government to overhaul the country’s centralized higher educational system, which fails to meet the needs of the country’s market economy and lags far behind international standards. For now, the strategies of Vietnamese universities and colleges are mainly driven by government planning. As the Agenda is nearing its end and tertiary institutions have completed a pilot project from 2014 to 2017 as part of HERA, it is time for Vietnamese higher education institutions to start reflecting on competitive strategies to prepare for necessary changes moving forward, ensuring their sustainable development and existence.